The Dynamics of Needs in a Course in English Phonetics for In-Service Primary School Teachers of English - Kapranov, Oleksandr (Theory and Practice of Second Language Acquisition, 2021)
This article presents a study that seeks to explore the dynamics of needs experienced by a group of in-service primary school teachers of English as a Foreign Language (EFL) who are enrolled in a course in English phonetics at a regional university in Norway. The course in English phonetics is designed for the group of EFL teachers (further – participants) who combine working full-time with taking in-service EFL courses. The aim of the study is to explore how the dynamics of the participants’ needs change within the time frame of two semesters. The study is based upon theoretical premises of needs analysis (further – NA) formulated by Hyland (2006), who regards EFL learners’ needs as a continuous process that changes over time. The results of NA indicate that whereas initially the participants explicitly express the need for obtaining tertiary-level education in English to be able to teach English at primary school, their needs change towards the end of the course to involve the focus on becoming role models in an EFL classroom, paying attention to speech fluency, intonation, and conducting English-only EFL classes. These findings will be further discussed in the article.